Temporal Retinal Nerve Fiber Loss in Patients with Spinocerebellar Ataxia Type 1 - Stricker, Sarah; Oberwahrenbrock, Timm; Zimmermann, Hanna; Schroeter, Jan; Endres, Matthias; Brandt, Alexander U.; Paul, Friedemann (PLOS ONE, 2011)
Background Autosomal dominant spinocerebellar ataxia type 1 is an adult onset progressive disorder with well characterized neurodegeneration in the cerebellum and brainstem. Beyond brain atrophy, few data exist concerning retinal and optic nerve involvement. Objective To evaluate retinal changes in SCA1 patients compared to age and gender matched healthy controls. Methodology/Principal Findings Nine patients with SCA1 were prospectively recruited from the ataxia clinic and were compared to nine age and gender matched healthy controls. Both cohorts received assessment of visually evoked potentials and eye examination by optical coherence tomography to determine retinal nerve fiber layer thickness and total macular volume. While no differences were found in visually evoked potentials, SCA1 patients showed a significant reduction of mean retinal nerve fiber layer thickness (RNFLT) compared to healthy controls (84±13 µm vs. 97±8 µm, p = 0.004). Temporal areas showed the most prominent RNFLT reduction with high statistical significances (temporal-inferior: p<0.001, temporal: p<0.001, temporal-superior: p = 0.005) whereas RNFLT in nasal areas was in the range of the control group. From six SCA1 patients an additional macular scan was obtained. The comparison to the corresponding healthy control showed a slight but not significant reduction in TMV (8.22±0.68 mm3 vs. 8.61±0.41 mm3, p = 0.15). Conclusion In SCA1 patients, we found evidence for degeneration of retinal nerve fibers. The temporal focus of the observed retinal nerve fiber layer reduction suggests an involvement of the papillo-macular bundle which resembles pathology found in toxic or mitochondrial optic nerve disease such as Leber's hereditary optic neuropathy (LHON) or dominant optic atrophy (DOA).